Evaluation of Aortic Diseases Using Four-Dimensional Flow Magnetic Resonance Imaging - Hyun Jung Koo; Hojin Ha; Gyu-Han Lee; Jong En Lee; Sang-hyub Park; Kyoung-jin Park; Joon-Won Kang; Dong Hyun Yang (Vascular Specialist International)
The complex hemodynamic environment within the aortic lumen plays a crucial role in the progression of aortic diseases such as aneurysms and dissections. Traditional imaging modalities often fail to provide comprehensive flow dynamics that are essential for precise risk assessment and timely intervention. The advent of time-resolved, three-dimensional (3D) phase-contrast magnetic resonance imaging (4D flow MRI) has revolutionized the evaluation of aortic diseases by allowing a detailed visualizations of flow patterns and quantification of hemodynamic parameters. This review explores the utility of 4D flow MRI in the assessment of thoracic aortic diseases, highlighting the key hemodynamic parameters, including flow velocity, wall shear stress, oscillatory shear index, relative residence time, vortex, turbulent kinetic energy, flow displacement, pulse wave velocity, aortic distensibility, energy loss, and stasis. We elucidate the significant findings of studies utilizing 4D flow MRI in the context of aortic aneurysms and dissections, highlighting its role in enhancing our understanding of disease mechanisms and improving clinical outcomes. This review underscores the potential of 4D flow MRI to refine risk stratification and guide therapeutic decisions, ultimately contributing to better management of aortic diseases.